Pharmacokinetics of sufentanil in the elderly surgical patient - Matteo, Richard S.; Schwartz, Arthur E.; Ornstein, Eugene; Young, William L.; Chang, Winjing (Canadian journal of anesthesia, 1990)
The effect of age on the distribution and elimination of sufentanil was studied in seven elderly (77 +/- 5 yr, mean +/- SD) and seven younger (41 +/- 15 yr) neurosurgical patients. Following a single IV bolus of sufentanil 2 micrograms.kg-1 multiple arterial samples were obtained at timed intervals and plasma concentrations of sufentanil were measured by radioimmunoassay. Pharmacokinetic variables were calculated from the derived compartmental models. The initial volume of distribution was significantly smaller in the elderly patients (310 +/- 109 ml.kg-1 vs 491 +/- 112 ml.kg-1 mean +/- SD). Elimination half-lives, plasma clearances, and total volumes of distribution were similar for elderly and younger subjects. Six of seven elderly patients required administration of naloxone at the termination of surgery to achieve an adequate rate of ventilation (greater than eight breaths.min-1) while only one younger patient required antagonism of ventilatory depression. The authors believe that age-related differences in the action of sufentanil cannot be accounted for by the observed differences in the initial volume of distribution. It is concluded that alterations in pharmacodynamics appear to be of greater importance in the prolonged opioid effect seen in the elderly.